Glucosinolate induces transcriptomic and metabolic reprogramming in Helicoverpa armigera - Jagdale, Shounak; Tellis, Meenakshi; Barvkar, Vitthal T.; Joshi, Rakesh S. (3 Biotech, 2021)
Glucosinolates protect plants from herbivory. Lepidopteran insects have developed resistance to glucosinolates which is well studied. However, the molecular effects of glucosinolate intake on insects are unexplored. To elucidate this, we performed transcriptomics and metabolomics of sinigrin-fed Helicoverpa armigera. Transcriptomics exhibits significant dysregulation of 2375 transcripts, of which 1575 are upregulated and 800 downregulated. Gene Ontology analysis of differentially expressed genes reveals that key hydrolases, oxidoreductases, and transferases are majorly affected. The negative impact of sinigrin is significant and localized in the endomembrane system and mitochondria. It also disturbs various biological processes such as regulation of protein metabolism and cytoskeletal organization. Furthermore, H. armigera putative myrosinase-like enzymes may catalyze the breakdown of sinigrin to allyl isothiocyanate (AITC). AITC targets the electron transport chain causing oxidative stress. KEGG pathway enrichment shows significant upregulation of oxidative phosphorylation, glutathione metabolism and amino acid metabolism. Activation of these pathways induces glutathione synthesis for sinigrin detoxification. Differential gene expression indicates upregulation of glutathione S-transferase and succinate dehydrogenase suggesting mitochondrial impact. Transcriptomics data correlated with metabolomics show changes in serine, methionine, ornithine, and other metabolite levels. It corroborates well with the transcript alterations supporting the increased glutathione production. Thus, our data suggest that sinigrin generates oxidative stress in H. armigera and insects alter their metabolic wiring to overcome sinigrin-mediated deleterious effects.
Keywords: Detoxification; Glucosinolate; Glutathione; mitochondria; Oxidative stress

Atomically dispersed manganese on graphene nanosheets as biocompatible nanozyme for glutathione detection in liver tissue lysate using microfluidic paper-based analytical devices - Baruah, Diksha J.; Thakur, Ashutosh; Roy, Esha; Roy, Kallol; Basak, Sumanjita; Neog, Dipankar; Bora, Himangsu K.; Konwar, Rituraj; Chaturvedi, Vikash; Shelke, Manjusha V.; Das, Manash R. (ACS Applied Materials & Interfaces, 2023)
Recently, single atom catalysts (SACs) featuring M-N-x (M = metal) active sites on carbon support have drawn considerable attention due to their promising enzyme-like catalytic properties. However, typical synthesis methods of SACs often involve energy-intensive carbonization processes. Herein, we report a facile one-pot, low-temperature, wet impregnation method to fully utilize M-N-4 sites of manganese phthalocyanine (MnPc) by decorating molecular MnPc over the sheets of graphene nanoplatelets (GNP). The synthesized MnPc@GNP exhibits remarkable peroxidase-mimic catalytic activity toward the oxidation of chromogenic 3,3 `,5,5(')-tetramethylbenzidine (TMB) substrate owing to the efficient utilization of atomically dispersed Mn and the high surface-to-volume ratio of the porous catalyst. A nanozyme-based colorimetric sensing probe is developed to detect important biomarker glutathione (GSH) within only 5 min in solution phase based on the ability of GSH to effectively inhibit the TMB oxidation. The high sensitivity and selectivity of the developed colorimetric assay enable us to quantitatively determine GSH concentration in different biological fluids. This work, for the first time, reports a rapid MnPc@GNP nanozyme-based colorimetric assay in the solid substrate by fabricating microfluidic paper-based analytical devices (mu PADs). GSH is successfully detected on the fabricated mu PADs coated with only 6.0 mu g of nanozyme containing 1.6 nmol of Mn in the linear range of 0.5-10 mu M with a limit of detection of 1.23 mu M. This work also demonstrates the quantitative detection of GSH in mice liver tissue lysate using mu PADs, which paves the way to develop mu PADs for point-of-care testing.
Keywords: colorimetricsensing; Glutathione; mu PADs; nanozyme; single atom catalyst; tissue lysate